Tinjauan Normatif terhadap Peran Satuan Polisi Pamong Praja dalam Perlindungan Aset Milik Pemerintah Daerah - Palindo, Ahmad Dempo; Ridlwan, Zulkarnain; Yusdianto, Yusdianto; Muhtadi, Muhtadi; Syofyan, Ahmad (VIVA THEMIS, 2025)
Local government assets are important resources that must be protected in order to support sustainable development and public services. The Local Government Police Unit (Satpol PP) plays a strategic role in securing local government assets, both through preventive and repressive measures. This study aims to conduct a normative analysis of the legal basis and scope of authority of the Satpol PP in securing local government assets, as well as its contribution in preventing the misuse and illegal occupation of such assets. The method used is a normative legal approach with a literature review of relevant laws and regulations, such as Law No. 23 of 2014 on Regional Government, Government Regulation No. 6 of 2010, as well as relevant regional regulations and governor regulations. The research findings indicate that the Satpol PP has clear and structured authority in securing local government assets, including supervision, enforcement, and administrative actions. Additionally, the Satpol PP's role in preventing asset misuse is carried out through routine patrols, public awareness campaigns, and cross-sectoral coordination. However, the effectiveness of implementing such authority still faces challenges such as limited resources and coordination among local government agencies